2019
DOI: 10.3389/fonc.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Organ Preservation in Rectal Cancer: The Patients' Perspective

Abstract: Organ preservation after a clinical complete response to radiochemotherapy is currently one of the most discussed topics in the management of rectal cancer. However, the patients' perspective has only been poorly studied so far. In this multicenter study, we examined 49 patients with locally advanced rectal cancer. The willingness to participate in an organ preservation study and the acceptance of the associated aspects such as intensified radiochemotherapy protocols, the need for close follow-up examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…The number of trials investigating novel strategies to improve responses to neoadjuvant treatment and to increase organ preservation rates that reported findings in 2020 [ 8 , 12 , 40 , 41 ] demonstrates the intense interest in this approach within the academic and clinical community. A recent survey of patients with rectal cancer in Germany has confirmed that treatment intensification to improve organ preservation rates is also a concept favoured by patients, even at the expense of toxicity from multi-modality non-surgical treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of trials investigating novel strategies to improve responses to neoadjuvant treatment and to increase organ preservation rates that reported findings in 2020 [ 8 , 12 , 40 , 41 ] demonstrates the intense interest in this approach within the academic and clinical community. A recent survey of patients with rectal cancer in Germany has confirmed that treatment intensification to improve organ preservation rates is also a concept favoured by patients, even at the expense of toxicity from multi-modality non-surgical treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are of highest clinical relevance. In the context of organ preservation strategies, the development of radiotherapy protocols that increase clinical complete response rates with limited toxicity and thus quality more patients for a “watch and wait” approach, are in the focus of research [ 26 ]. According to the standards of the time when the trial was initiated, surgery was scheduled four to six weeks after the end of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on neoadjuvant treatment for rectal cancer, it is expected some patients with a cCR will be reluctant to undergo surgery. Indeed, cCR patients at our institution are typically offered the option of non-operative management and close surveillance [26] . We thus reported a combined pCR/cCR rate and considered this value appropriate for future trial design.…”
Section: Discussionmentioning
confidence: 99%